Introducing results-based approaches in agriculture: challenges and lessons learnt - Heiner Janus; Sarah Holzapfel (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
Increased and more effective public and private investments in the agricultural sector are needed to achieve the goals of ending hunger and reaching food security by 2030. Results-based approaches, which are innovative financing modalities that link payments to pre-defined results, are potentially powerful tools for overcoming the food security challenge. Results-based approaches promise several advantages over traditional aid modalities, to include a greater focus on results, better accountability systems and improved incentives. They can also be an important tool for accelerating innovation and leveraging additional resources from private investors for agricultural and food security interventions. While widely applied in the health and education sectors, only few experiences with results-based approaches in agriculture exist, and the suitability of the sector for the instrument is debated. Our briefing paper contributes to this debate by: laying out the challenges to implementing results-based approaches in the agricultural sector; introducing the Five Rural Worlds model (5RW) (OECD, 2006) as a framework for analysis of targeting and interdependencies; and summarising first experiences from pilot programmes. We briefly review three pilot interventions representing different types of results-based approaches: results-based aid (a contract between governments) in Rwanda, results-based finance (a contract between a funder/host-country government and a service provider) in Zambia, and development impact bonds (DIBs) (a contract between a funder, a service provider, and a private investor) in Peru. The analysis of the three pilot programmes shows that results-based approaches have the potential to foster innovation in agriculture and to play an important role in improving food security in developing countries. Results-based aid programmes can provide additional incentives for partner country governments to focus on agricultural innovation and on reducing hunger and malnutrition in the long run. Results-based finance programmes, by offering economic incentives to service providers or private companies, can help to overcome market failures and foster the adoption of new technologies. DIBs are a novel way to engage private actors in addressing development challenges. However, our analysis also shows that implementing results-based approaches in agriculture is challenging because of the complexity of measuring and achieving results in the sector. First, desired outcomes such as increased yields or incomes are highly variable and influenced by external conditions (e.g. weather and world market prices). Second, agriculture is a productive sector. Market forces and private actors play a much more important role in agriculture than in health or education. Improving agricultural productivity and food security relies on the decisions of millions of farmers and enterprises. Hence, designing results-based incentives and deciding whom to target is much more complex than in sectors dominated by the government. Using the 5RW model, which distinguishes between five types of rural actors, ranging from chronically poor households to large commercial agricultural enterprises, we find that results-based approaches should take into account interrelations between the RWs.
Keywords: 330; Landwirtschaft und ländliche Entwicklung; Wirksamkeit und Evaluierung